Release of intermediate reactive hydrogen peroxide by macrophage cells activated by natural products - Moreira, RRD; Carlos, I. Z.; Vilegas, Wagner [UNESP] (Pharmaceutical Soc Japan, 2001)
By determining the hydrogen peroxide (H2O2) released in cultures of peritoneal macrophage cells from Swiss mice, we evaluated the action of 27 vegetable compounds (pristimerin, tingenone, jatrophone, palustric acid, lupeol, cladrastin, ocoteine, boldine, tomatine, yohimbine, reserpine, escopoletin, esculine, plumericin, diosgenin, deoxyschizandrin, p-arbutin, mangiferin, and others) using a 2 mg/ml solution of each compound (100 mug/well). Macrophages are cells responsible for the development of the immunological response reaction, liberating more than one hundred compounds into the extracellular environment. Among these are the various cytokines and the intermediate compounds of nitrogen (NO) and oxygen (H2O2). This coordinated sequence of biochemical reactions is known as the oxidative burst. When we compared the results with those obtained with zymosan (an important stimulator of H2O2) we observed that the compounds showing the highest activity were substances 2 (tingenone), 16 (reserpine) and 20. Other substances such as compounds 1, 4, 5, 6, 8, 12, 13, 14, 15, 17, 19, 23, 24, 26, and 27 also showed a certain activity, but with less intensity than the aforementioned ones. Compounds 3, 7, 9, 10, 11, 18, 21, 22 and 25 presented no activity. These results suggest that natural products (mainly tingenone and reserpine and others) with different chemical structures are strong immunological modulators. However, further tests are needed to determine the 'oxidative burst' in future studies.
Keywords: natural product; macrophage; hydrogen peroxide